Hubungan Motivasi Kerja dan Self Efficacy dengan Tingkat Burnout Perawat di Rumah Sakit Islam Sultan Agung Semarang - Wahyu Cakra Dafitrianto; Dyah Wiji Puspita Sari; Retno Issroviatiningrum (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Burnout among nurses is a serious problem that can reduce the quality of nursing services and the well being of nurses. Work motivation and self efficacy are psychological factors that play an important role in reducing burnout. The aim is to minimize the occurrence of burnout among nurses in their performance.The purpose of this study is to determine the significance of the relationship between work motivation and self efficacy with the level of burnout among nurses. This research is quantitative in nature with a cross-sectional approach. Data collection was conducted using questionnaires administered to 98 respondents from the total population. The instruments used included a work motivation questionnaire (ERG), a general self-efficacy scale (GSES), and a Maslach Burnout Inventory (MBI). The data collected was processed using Spearman's test and ordinal logistic regression. Results researchers found that respondents who reported high work motivation numbered 89 respondents with a percentage of (90.8%), self-efficacy among nurses also showed a high category in 90 respondents with a percentage of (91.8%), and the majority of burnout levels were in the low category range of 65 respondents with a percentage of (66.4). Statistical tests showed a relationship between work motivation and burnout levels with a p-value of 0.000 (a = -0.358), and showed that there was a relationship between self-efficacy and burnout levels with a p-value of 0.013 (a = -0.250). Furthermore, multivariate statistics found that work motivation was the dominant factor influencing burnout with a p-value of 0.012 (E = -2.030). Conclusion there is a significant relationship between work motivation and self-efficacy with the level of burnout among nurses. Nurses with high work motivation and self-efficacy tend to have lower levels of burnout. Work motivation is a dominant factor in influencing burnout.